CORPORATE CULTURE DEVELOPMENT BY MEANS OF EFFICIENT COMMUNICATIONS ORGANIZATION - Albina Danilova; Olga Fedorova; Svetlana Zdrestova-Zakharenkova (Вестник Северо-Кавказского федерального университета)
This article touches on the problems of development of corporate culture through effective communication; summarize the approaches on the issue of correlation of concepts «organizational» and «corporate» culture; the structure of the object of research through the integration of views of D. A. Leontiev and E. Shane. The orientation of management decisions in the formation of stages of development of corporate culture for the effective management of communications, as one of the elements ofprocess subsystems.